Kurikulum Kristen untuk Pembentukan Karakter: Landasan untuk Pertumbuhan Rohani dan Akademik - Cung, Liuw Tjhin Dji; Lau, Peter; Yulianawati, Yulianawati (INTELEKTIUM, 2025)
Christian education is not only about imparting academic knowledge but also about forming character that reflects Christ. This article emphasizes that Christian curriculum for character building must stand on three pillars: (1) educators must be believers with a growing Christian life, (2) the curriculum should focus on developing students’ Christian character alongside academic excellence, and (3) schools must intentionally create a Christian environment that reflects biblical values. By combining theological reflection with practical educational insights, this study highlights the vital role of teachers as role models, the integration of biblical truth into learning, and the importance of school culture in shaping students’ faith. The results suggest that effective Christian curriculum leads to holistic development—equipping students academically, spiritually, and morally to live faithfully in a complex world.